The Role of Leadership Capabilities in Mediating Job Satisfaction and Core Competence on Business Performance - Dewi, Ni; Merta, I Ketut; Suparta, I Nyoman (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Rural economic institutions play a crucial role in local economies but also pose challenges to achieving economic self-sufficiency in rural areas. This study focuses on Village-Owned Enterprises (Badan Usaha Milik Desa or BUMDes) in Tabanan Regency, Bali, where their increasing presence warrants an in-depth evaluation. Specifically, the research aims to investigate the impact of leadership competence and job satisfaction on BUMDes' business performance. The study utilizes quantitative methods and data analysis through SPSS V24. The findings indicate that leadership capabilities, core competence, and job satisfaction significantly influence business performance. Leadership capabilities play a mediating role in the relationship between core competence and business performance, as well as between job satisfaction and business performance. These results provide valuable insights for BUMDes in Tabanan Regency to enhance their effectiveness and impact on rural economic development. These results provide valuable insights for BUMDes in Tabanan Regency to enhance their effectiveness and impact on rural economic development. The study suggests that, to improve the performance and impact of BUMDes, these organizations should focus on leadership development, core competence enhancement, and measures to enhance job satisfaction among their members. ABSTRAK Lembaga ekonomi pedesaan memainkan peran penting dalam perekonomian lokal namun juga menimbulkan tantangan dalam mencapai swasembada ekonomi di daerah pedesaan. Penelitian ini berfokus pada Badan Usaha Milik Desa (BUMDes) di Kabupaten Tabanan, Bali, di mana keberadaan mereka yang semakin meningkat memerlukan evaluasi mendalam. Secara khusus, penelitian ini bertujuan untuk menyelidiki dampak kompetensi kepemimpinan dan kepuasan kerja terhadap kinerja bisnis BUMDes. Penelitian ini menggunakan metode kuantitatif dan analisis data melalui SPSS V24. Temuan menunjukkan bahwa kemampuan kepemimpinan, kompetensi inti, dan kepuasan kerja secara signifikan memengaruhi kinerja bisnis. Kemampuan kepemimpinan memainkan peran mediasi dalam hubungan antara kompetensi inti dan kinerja bisnis, serta antara kepuasan kerja dan kinerja bisnis. Hasil ini memberikan wawasan berharga bagi BUMDes di Kabupaten Tabanan untuk meningkatkan efektivitas dan dampaknya pada pengembangan ekonomi pedesaan. Penelitian ini menyarankan bahwa, untuk meningkatkan kinerja dan dampak BUMDes, organisasi-organisasi ini sebaiknya berfokus pada pengembangan kepemimpinan, peningkatan kompetensi inti, dan langkah-langkah untuk meningkatkan kepuasan kerja di antara anggotanya. Kata kunci: BUMDes, Pengembangan Ekonomi Pedesaan, Kemampuan Kepemimpinan, Kompetensi Inti, Kepuasan Kerja